Fertility knowledge, care seeking behavioral pattern and attitudes of infertile men in Lagos, Nigeria - Enwuru, Christian A.; Iwalokun, Bamidele; Enwuru, Veronica N.; Oparaugo, Chinedum T.; Ezechi, Oliver; Oluwadun, Afolabi (International Journal of Research in Medical Sciences, 2020)
Background: The objective was to study the extent of infertility knowledge, attitude and care seeking behavioral pattern of infertile men in Lagos. Methods: A cross sectional study was carried out using questionnaire between 2009 and 2014. Adult males who were clinically infertile, visiting the clinics for the first time and consented were studied. Descriptive statistics were used for the analysis. Results: Only 226 men, mean age 38±5.8 years participated. Up to 20.8% had sired a child for between >1 but <2, 20.4% for 2-5 and 58.8% for ≥6 years. Couples had coitus for once and >3 times (mean coitus 2.3±0.9 times) weekly. Only 11.1% knew about male-female factor infertility. Up to 42.9% knew about fertility and the sign of female ovulation and 38.1% correctly defined clinical infertility. Up to 40.3% switched treatment for competency of the new places and exorbitant price by 22.1%. Sixty-six (29.2%) made the first visit to a proper care place within a period >1 but <2 years, 45.1% within 2-3 years and 25.7% waited for >3 years. Majority (50 %) sought to know the causes of infertility, 14.6% how to improve fertility and 6.6% the reality of male infertility. Conclusions: Majority of the participants sought inappropriate help and delayed in seeking appropriate care. Poor collaboration and referral system observed. There is need for edification of both care providers and seekers to be ethical in their actions. Infertility care cost intervention is needed.